ANALYSIS OF PERIODIC TESTING FOR FREIGHT VEHICLES REGULATIONS - Muhammad Triardya Wiratama; Catharina Dewi Wulansari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study is motivated by the increasing number of traffic accidents caused by vehicle technical failures , primarily due to the ineffective implementation of periodic vehicle inspections . Periodic testing serves as a strategic legal instrument to ensure the roadworthiness of freight vehicles in terms of safety , operational efficiency , and environmental protection . However , the effectiveness of such regulations remains problematic , both in terms of normative quality and practical implementation . This research aims to analyze the legal framework governing periodic testing of freight vehicles and to evaluate its regulatory quality based on the standards of good legislation . This study employs a normative juridical method with statutory and conceptual approaches . The findings indicate that although several regulations exist , fundamental weaknesses remain in procedural provisions , supervision , authority , and sanctions that failed to provide deterrent effects . The novelty of this research lies in its comprehensive evaluation of legal norms using clarity of law and adequacy indicators , linked to legal effectiveness in practice . This study concludes that legal policy reform is required through stronger sanction mechanisms , improved supervisory systems , and institutional harmonization to enhance compliance and reduce traffic accidents .